THE BRICS IN THE SPOTLIGHT: A RESEARCH AGENDA - L. Scaffardi; V. Federico (BRICS Law Journal)
On November 6–7, 2014, the University of Parma (Italy) hosted a profound two-day discussion on the BRICS, i.e. Brazil, Russia, India, China and South Africa, a relatively new actor in the international arena, gathering the most innovative research and the leading experts and scholars.